Weathering steel for coating-free photovoltaic support, preparation method of weathering steel and coating-free photovoltaic support

By using weathering steel with specific chemical composition and tissue structure in the photovoltaic scaffold, the problem of photovoltaic scaffold corrosion in the marine environment is solved, and good weather resistance and mechanical properties are achieved in high salt and high humidity environments.

CN119392116APending Publication Date: 2025-02-07HUNAN VALIN LIANYUAN IRON & STEEL CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411518339.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In marine environments, photovoltaic stents are susceptible to corrosion by NaCl particles in the atmosphere, resulting in surface passivation and damage, seriously affecting its weathering performance and service life.

Method used

Using a specific weathering steel, its chemical composition includes carbon, silicon, manganese, phosphorus, titanium, chromium, copper, molybdenum, aluminum, antimony and other elements, through fine smelting and rolling processes, it forms 5% to 15%. Steel with ferrite and 85% to 95% bainite biphasic composite structure.

Benefits of technology

This weathering steel exhibits good weather resistance and mechanical properties in a coastal high-salt and high-humidity corrosion environment, with a small thickness reduction and a weathering index greater than 8.0, meeting the needs of coating-free photovoltaic brackets.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119392116A_ABST
    Figure CN119392116A_ABST
Patent Text Reader

Abstract

The weathering steel for the coating-free photovoltaic support comprises the following chemical components in percentage by mass: 0.07 percent to 0.09 percent of carbon, 0.20 percent to 0.30 percent of silicon, 1.0 percent to 1.1 percent of manganese, less than or equal to 0.003 percent of sulfur, 0.07 percent to 0.09 percent of phosphorus, 0.040 percent to 0.065 percent of titanium, 1.0 percent to 1.1 percent of chromium, 0.23 percent to 0.28 percent of copper, 0.12 percent to 0.16 percent of molybdenum, 0.55 percent to 0.65 percent of aluminum, 0.08 percent to 0.12 percent of antimony and the balance of iron and inevitable impurities. The steel comprises the following components in percentage by weight: less than or equal to 0.0045% of nitrogen, less than or equal to 0.0015% of oxygen, less than or equal to 0.00015% of hydrogen and the balance The thickness of the weathering steel for the coating-free photovoltaic support is smaller than or equal to 6.0 mm. The weather-resistant steel for the coating-free photovoltaic bracket has good mechanical properties, has good weather resistance in a coastal high-salinity and high-humidity corrosive environment, and is relatively small in thickness reduction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of steel plate smelting, and specifically relates to a weathering steel for a paint-free photovoltaic bracket and a preparation method thereof, and a paint-free photovoltaic bracket. Background Art

[0002] The coastal areas are vast and rich in wind and solar energy resources. With the increasing development of new energy, steel structures are widely used, and the application of steel such as photovoltaic brackets is also promoted.

[0003] In harsh marine environments, the corrosion problem of photovoltaic brackets is more prominent. NaCl particles carried in the coastal atmosphere are easy to deliquesce on the surface of steel components such as photovoltaic brackets, increase the conductivity of the electrolyte, destroy the surface passivation of the steel, and cause the most serious atmospheric corrosion. Therefore, it is of great significance to improve corrosion resistance, use bare without painting, and reduce the later anti-corrosion costs. Summary of the invention

[0004] In view of this, the present application provides a weathering steel for a paint-free photovoltaic bracket and a preparation method thereof, and a paint-free photovoltaic bracket, aiming to provide a weathering steel for a paint-free photovoltaic bracket having good mechanical properties, good weather resistance in the coastal high-salt and high-humidity corrosion environment, and less thickness reduction.

[0005] In the first aspect, an embodiment of the present application provides a weathering steel for a paint-free photovoltaic bracket, and the chemical composition of the weathering steel for a paint-free photovoltaic bracket includes, by mass percentage: carbon: 0.07%-0.09%, silicon: 0.20%-0.30%, manganese: 1.0-1.1%, sulfur ≤0.003%, phosphorus: 0.07%-0.09%, titanium: 0.040%-0.065%, chromium: 1.0%-1.1%, copper: 0.23%-0.28%, molybdenum: 0.12%-0.16%, aluminum: 0.55%-0.65%, antimony: 0.08%-0.12%, nitrogen ≤0.0045%, oxygen ≤0.0015%, hydrogen ≤0.00015%, and the rest are Fe and unavoidable impurity elements; the thickness of the weathering steel for a paint-free photovoltaic bracket is ≤6.0mm.

[0006] According to an embodiment of one aspect of the present application, the chemical composition of the weathering steel for the paint-free photovoltaic bracket includes, by mass percentage: carbon: 0.075%-0.085%, silicon: 0.20%-0.30%, manganese: 1.0-1.1%, sulfur ≤0.003%, phosphorus: 0.07%-0.09%, titanium: 0.040%-0.065%, chromium: 1.0%-1.1%, copper: 0.23%-0.28%, molybdenum: 0.13%-0.15%, aluminum: 0.58%-0.62%, antimony: 0.08%-0.12%, nitrogen ≤0.0045%, oxygen ≤0.0015%, hydrogen ≤0.00015%, and the rest are Fe and unavoidable impurity elements.

[0007] According to an embodiment of one aspect of the present application, the weathering index of the weathering steel for coating the photovoltaic bracket is greater than 8.0.

[0008] According to an embodiment of one aspect of the present application, the metallographic structure of the weathering steel for coating photovoltaic brackets includes a two-phase composite structure of 5% to 15% ferrite and 85%-95% bainite by volume fraction; the grain size of the weathering steel for coating photovoltaic brackets is 8 to 10.

[0009] According to an embodiment of one aspect of the present application, the yield strength of the weathering steel for the paint-free photovoltaic bracket is greater than or equal to 550MPa, the tensile strength is greater than or equal to 600MPa, the elongation is greater than or equal to 16%, and the -20°C KV2 impact energy is greater than or equal to 47J.

[0010] In a second aspect, an embodiment of the present application provides a method for preparing weathering steel for a paint-free photovoltaic bracket according to the first aspect, the method comprising:

[0011] The molten steel is subjected to converter smelting to obtain converter molten steel;

[0012] The converter molten steel is subjected to LF refining and RH vacuum treatment to obtain tundish molten steel;

[0013] Continuously casting the molten steel in the tundish to obtain a slab;

[0014] The slab is heated, rolled, laminar-cooled and coiled to obtain the weathering steel for the coating-free photovoltaic support;

[0015] The rolling includes rough rolling and finish rolling, the temperature of the rough rolling start is 1150-1180°C, the temperature of the rough rolling final rolling is 1050-1090°C, the temperature of the finish rolling start is 1030-1070°C, the finish rolling final rolling is 890-910°C, and laminar cooling is carried out after the final rolling, and the final cooling is carried out to 575-590°C for coiling.

[0016] According to an embodiment of one aspect of the present application, after the converter smelting, the method further comprises: passing the converter molten iron through a ladle and blowing argon, and the temperature controlled at the end point of the argon station is greater than 1535°C.

[0017] According to an embodiment of one aspect of the present application, RH vacuum treatment includes: vacuum degree requirement ≤133MPa, RH cycle time 20-30min, RH outgoing pouring furnace temperature is 1570-1580℃, and RH outgoing continuous pouring temperature is 1558-1580℃.

[0018] According to an embodiment of one aspect of the present application, the heating temperature includes 1180-1230° C., and the temperature is kept constant for more than 20 minutes.

[0019] According to an embodiment of one aspect of the present application, the cooling rate of the laminar cooling is 20-30°C / s.

[0020] In a third aspect, an embodiment of the present application provides a paint-free photovoltaic bracket, which is obtained by processing the weathering steel for the painted photovoltaic bracket of the first aspect or the weathering steel for the paint-free photovoltaic bracket obtained by the preparation method of the second aspect.

[0021] This application has at least the following beneficial effects:

[0022] The weathering steel for painted photovoltaic brackets provided in the present application, on the basis of adding a large amount of traditional chromium, nickel, molybdenum, and copper elements to improve corrosion resistance, replaces precious nickel with more economical aluminum, and reduces the molybdenum content of weathering steel in traditional marine environments from about 0.5% to 0.12-0.18%, replaces part of the molybdenum with a trace amount of antimony, and adds economical phosphorus elements to make up for the weathering index of nickel saving, ensuring that the weathering index I ≥ 8.0. By adding 0.07-0.09% P, the weathering steel for unpainted photovoltaic brackets has good mechanical properties, and has good weather resistance in the high-salt and high-humidity corrosion environment of the coast, with less thickness reduction. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solution of the implementation regulations of this application, the following is a brief introduction to the drawings required for use in the embodiments of this application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without any creative work.

[0024] Figure 1 A micrograph of weathering steel for a paint-free photovoltaic support having a thickness of 2 mm according to an embodiment of the present application is shown.

[0025] Figure 2 A micrograph of weathering steel for a paint-free photovoltaic support having a thickness of 4 mm according to an embodiment of the present application is shown.

[0026] Figure 3The corrosion morphology of weathering steel for paint-free photovoltaic brackets in the embodiments and comparative examples of the present application is shown. DETAILED DESCRIPTION

[0027] In order to make the application purpose, technical solution and beneficial technical effect of this application clearer, the application is further described in detail below in conjunction with the embodiments. It should be understood that the implementation regulations described in this specification are only for explaining this application, not for limiting this application.

[0028] For simplicity, the present application only explicitly discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an unclearly recorded range; and any lower limit can be combined with other lower limits to form an unclearly recorded range, and any upper limit can be combined with any other upper limit to form an unclearly recorded range. In addition, although not clearly recorded, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unclearly recorded range.

[0029] In the description of the present application, it should be noted that, unless otherwise specified, “above” and “below” are inclusive of the number, and the “multiple” in “one or more” means two or more than two.

[0030] The above application content of the present application is not intended to describe each disclosed embodiment or each implementation in the present application. The following description more specifically illustrates exemplary embodiments. In many places throughout the application, guidance is provided through a series of embodiments, and these implementation regulations can be used in various combinations. In each example, enumeration is only used as a representative group and should not be interpreted as exhaustive.

[0031] Weathering steel for paint-free photovoltaic support

[0032] In the first aspect, an embodiment of the present application provides a weathering steel for a paint-free photovoltaic bracket, and the chemical composition of the weathering steel for a paint-free photovoltaic bracket includes, by mass percentage: carbon: 0.07%-0.09%, silicon: 0.20%-0.30%, manganese: 1.0-1.1%, sulfur ≤0.003%, phosphorus: 0.07%-0.09%, titanium: 0.040%-0.065%, chromium: 1.0%-1.1%, copper: 0.23%-0.28%, molybdenum: 0.12%-0.16%, aluminum: 0.55%-0.65%, antimony: 0.08%-0.12%, nitrogen ≤0.0045%, oxygen ≤0.0015%, hydrogen ≤0.00015%, and the rest are Fe and unavoidable impurity elements; the thickness of the weathering steel for a paint-free photovoltaic bracket is ≤6.0mm.

[0033] The present application adopts weathering steel for painting-free photovoltaic brackets with a thickness of ≤6.0mm, in which the precious nickel is replaced by more economical aluminum on the basis of adding a large amount of traditional chromium, nickel, molybdenum and copper elements to improve corrosion resistance, and the molybdenum content of weathering steel in traditional marine environment is reduced from about 0.5% to 0.12-0.18%, and a trace amount of antimony is used to replace part of the molybdenum. Economic phosphorus elements are added to make up for the weathering index of nickel saving, and 0.07-0.09% P is added, so that the weathering steel for painting-free photovoltaic brackets has good mechanical properties, and the total thinning in 25 years in the coastal climate environment of Zhanhua, Binzhou, Shandong does not exceed 0.5mm.

[0034] In this embodiment, the chemical composition design concept of weathering steel for paint-free photovoltaic bracket is:

[0035] Carbon: Low carbon content design can significantly increase the phase transformation temperature, which is conducive to the formation of proeutectoid ferrite. Low carbon design can reduce component segregation, ensure the uniformity of the organization, and improve corrosion resistance and welding performance. A certain content of carbon can ensure the precipitation of the second phase of carbide and the strength and welding performance of the steel plate. The carbon content is controlled at 0.07-0.09%.

[0036] Silicon: Silicon can be deoxidized during the smelting process, but too high a content will affect weldability and toughness. Its content is controlled at 0.20-0.30%.

[0037] Manganese: Manganese is beneficial to improving high-temperature brittleness and easily forms MnS inclusions. MnS inclusions are harmful to impact toughness, corrosion resistance, and welding performance. Its content is controlled at 1.0-1.10%.

[0038] Sulfur: Sulfur easily forms MnS inclusions in steel. Too much sulfur easily forms TiSC4 coarse carbides in titanium-containing steel, which is unfavorable to corrosion performance. Its content is in the range of 0.02-0.035%.

[0039] Phosphorus: Excessive phosphorus will cause grain boundary segregation and increase the low-temperature brittleness of steel. A small amount of phosphorus can increase the weather resistance of steel. The phosphorus content is controlled at 0.07-0.09%.

[0040] Titanium: During the continuous casting solidification process, titanium combines with nitrogen to form TiN, reducing the effect of nitrogen on boron. The presence of TiN can inhibit the coarsening of grains in the heat affected zone of welding. The Ti content is 0.040-0.065%.

[0041] Aluminum: The addition of a certain amount of aluminum forms Al2O3, which is beneficial to the formation of α-Fe2O3 that improves the density of weathering steel and is beneficial to improving corrosion resistance. Excessive aluminum addition will result in δ ferrite with coarse grains, which is not conducive to recrystallization. The addition of Al can replace part of the Ni element, thereby reducing costs.

[0042] Chromium: The addition of a certain amount of chromium can control the formed Cr2O3 at 1.0-1.1%, which can promote a denser rust layer structure, ensure good isolation between the matrix and the medium, and is also an important element for improving the corrosion resistance index.

[0043] Copper: Adding 0.23-0.28% copper can increase the electrode potential of the substrate, embed into Fe2O3 in the form of CuO and Cu2O in the rust layer, and promote α-Fe2O3.

[0044] Molybdenum: Mo is beneficial to the refinement of ferrite and improves the yield strength of steel, but it also improves the yield strength ratio of steel and can increase the ability of the rust layer or passivation film to resist chloride ion corrosion. The mass content of Mo is about 0.12-0.16%.

[0045] Antimony: Antimony is the chemical element that has the most significant effect in improving the corrosion resistance of steel in a chloride ion environment, and Sb significantly improves the corrosion resistance of steel. However, Sb is an element that has an adverse effect on the strength, toughness, plasticity and weldability of steel. Sb added to the metal surface can form Sb2O5 in the corrosive medium, which has higher stability than the steel matrix, and prevents the steel matrix from being further corroded by the corrosive medium. In the present invention, the antimony content is controlled at 0.08-0.12%, and it couples with Cu and Mo, has good corrosion resistance, and does not damage toughness. Sb, Cu and Mo can form an oxide film on weathering steel for coated photovoltaic brackets, which is beneficial to improve weather resistance, so that weathering steel for unpainted photovoltaic brackets can maintain its thickness in the coastal climate environment of Zhanhua, Binzhou, Shandong, and the total thinning does not exceed 0.5mm.

[0046] Gaseous elements such as nitrogen, oxygen, and hydrogen are extremely detrimental to the performance stability of steel and should be strictly controlled: nitrogen ≤ 0.0045%, oxygen ≤ 0.0015%, and hydrogen ≤ 0.00015%.

[0047] In some optional embodiments, the chemical composition of the weathering steel for the unpainted photovoltaic bracket includes, by mass percentage: carbon: 0.075%-0.085%, silicon: 0.20%-0.30%, manganese: 1.0-1.1%, sulfur ≤0.003%, phosphorus: 0.07%-0.09%, titanium: 0.040%-0.065%, chromium: 1.0%-1.1%, copper: 0.23%-0.28%, molybdenum: 0.13%-0.15%, aluminum: 0.58%-0.62%, antimony: 0.08%-0.12%, nitrogen ≤0.0045%, oxygen ≤0.0015%, hydrogen ≤0.00015%, and the rest are Fe and unavoidable impurity elements. Therefore, the ability of the weathering steel for the unpainted photovoltaic bracket to maintain thickness in the coastal climate environment of Zhanhua, Binzhou, Shandong is further improved, and the total thinning does not exceed 0.5mm.

[0048] In some optional embodiments, the weathering index of the weathering steel for coating the photovoltaic support is greater than 8.0. Therefore, the weathering performance is improved while taking into account the economic benefits.

[0049] In this embodiment, the calculation formula of the corrosion resistance index (CI) can be: CI = 0.10 × C + 0.20 × Si + 0.30 × Cu + 0.50 × Cr + 0.20 × Ni

[0050] Among them, C represents the mass content (%) of carbon, Si represents the mass content (%) of silicon, Cu represents the mass content (%) of copper, Cr represents the mass content (%) of chromium, and Ni represents the mass content (%) of nickel.

[0051] In some optional embodiments, the metallographic structure of the weathering steel for coating photovoltaic brackets includes a two-phase composite structure of 5% to 15% ferrite and 85%-95% bainite by volume fraction; the grain size of the weathering steel for coating photovoltaic brackets is 8 to 10.

[0052] According to the embodiment of the present application, the substructure of the bainite structure in the weathering steel for photovoltaic brackets is refined, and a trace amount of titanium with good economical precipitation is added to strengthen and ensure strength; because the composition of weathering steel and high-strength steel is optimized, the ratio of each element is matched with the composition preparation process. Weathering steel for photovoltaic brackets without painting suitable for coastal climate environments is prepared.

[0053] In some optional embodiments, the yield strength of the weathering steel for the paint-free photovoltaic bracket is greater than or equal to 550MPa, the tensile strength is greater than or equal to 600MPa, the elongation is greater than or equal to 16%, and the -20℃K V2 impact energy is greater than or equal to 47J.

[0054] Preparation method of weathering steel for coating-free photovoltaic support

[0055] In a second aspect, an embodiment of the present application provides a method for preparing weathering steel for a paint-free photovoltaic bracket according to the first aspect, the method comprising:

[0056] The molten steel is subjected to converter smelting to obtain converter molten steel;

[0057] The converter molten steel is subjected to LF refining and RH vacuum treatment to obtain tundish molten steel;

[0058] Continuously casting the molten steel in the tundish to obtain a slab;

[0059] The slab is heated, rolled, laminar-cooled and coiled to obtain the weathering steel for the coating-free photovoltaic support;

[0060] The rolling includes rough rolling and finish rolling, the temperature of the rough rolling start is 1150-1180°C, the temperature of the rough rolling final rolling is 1050-1090°C, the temperature of the finish rolling start is 1030-1070°C, the finish rolling final rolling is 890-910°C, and laminar cooling is carried out after the final rolling, and the final cooling is carried out to 575-590°C for coiling.

[0061] According to the embodiment of the present application, the above-mentioned method is adopted to control rolling and laminar cooling, and the best mechanical effect is obtained through the coupling effect of deformation recrystallization in the high-temperature austenite zone, deformation in the low-temperature austenite non-recrystallization zone, and accelerated cooling after rolling. In the high-temperature austenite zone, corrosion-resistant elements such as Cr, Ni, Cu, Mo, Sb, and Al are dissolved into the matrix, and the rolling and controlled cooling technology are controlled to ensure that the alloy elements are in a solid solution state and that the passivation film has sufficient alloy elements to participate in forming a film on the surface of weathering steel for coating-free photovoltaic brackets, which is beneficial to improve the mechanical properties and weather resistance of weathering steel for coating-free photovoltaic brackets, and reduce its thickness reduction in coastal environments.

[0062] Generally speaking, the production process of weathering steel for paint-free photovoltaic brackets generally includes converter smelting, LF furnace refining, RH furnace refining or RH road vacuum treatment, continuous casting to obtain slabs, slab heating, rough rolling, finishing rolling, laminar cooling, steel plate coiling, steel coil stacking cooling, cross-cutting and flattening, inspection and warehousing.

[0063] In some optional embodiments, the tundish molten steel is continuously cast, and after the pouring is normal, the pulling speed is ≥0.8m / min, and can be selected as 0.9-1.4m / min. The above pulling speed can be slowly raised and lowered, and the casting adopts a light pressure reduction mode. The casting is piled and cooled to room temperature, the slab is heated in a furnace, and then rolled by a rough rolling unit for 7 passes, and then enters a laminar cooling system after rolling to achieve the purpose of controlling the metallographic structure of the steel plate.

[0064] In some optional embodiments, after the converter smelting, the method further comprises: passing the converter molten iron through a ladle and blowing argon, and the temperature controlled at the end point of the argon station is greater than 1535°C.

[0065] In some optional embodiments, the RH vacuum treatment includes: vacuum degree requirement ≤ 133MPa, RH cycle time 20-30min, RH outgoing pouring furnace temperature 1570-1580℃, RH outgoing continuous pouring temperature 1558-1580℃.

[0066] In some optional embodiments, the heating temperature includes 1180-1230°C, and the temperature is kept constant for more than 20 minutes at this temperature. In some optional embodiments, the entire slab heating includes preheating, target heating, and solid solution, and the total heating time of the entire slab is 160-250 minutes. The solid solution temperature can be 1180-1230°C, and the solid solution time can be more than 20 minutes.

[0067] In some optional embodiments, the cooling rate of the laminar cooling is 20-40°C / s. With the above cooling rate, i.e., with a cooling rate compared to the traditional process, the ferrite in the slab begins to transform at a temperature of 660°C, the temperature at which the ferrite transformation ends is 590°C, and pearlite transformation occurs below 580°C, so that the weathering steel for the coated photovoltaic bracket can obtain a suitable volume ratio of bainite and ferrite, thereby improving the mechanical properties and weather resistance of the weathering steel for the coated photovoltaic bracket.

[0068] In a third aspect, an embodiment of the present application provides a paint-free photovoltaic bracket, which is obtained by processing the weathering steel for the painted photovoltaic bracket of the first aspect or the weathering steel for the paint-free photovoltaic bracket obtained by the preparation method of the second aspect.

[0069] Example

[0070] The following examples describe the disclosure of the present application in more detail, and these examples are intended for illustrative purposes only, as it will be apparent to those skilled in the art that various modifications and variations may be made within the scope of the disclosure of the present application. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.

[0071] Examples 1-3 and Comparative Examples 1-4

[0072] An embodiment of the present application provides a weathering steel for a paint-free photovoltaic bracket, and the chemical composition of the weathering steel for a paint-free photovoltaic bracket includes, by mass percentage: carbon: 0.07%-0.09%, silicon: 0.20%-0.30%, manganese: 1.0-1.1%, sulfur ≤0.003%, phosphorus: 0.07%-0.09%, titanium: 0.040%-0.065%, chromium: 1.0%-1.1%, copper: 0.23%-0.28%, molybdenum: 0.12%-0.16%, aluminum: 0.55%-0.65%, antimony: 0.08%-0.12%, nitrogen ≤0.0045%, oxygen ≤0.0015%, hydrogen ≤0.00015%, and the rest are Fe and unavoidable impurity elements; the thickness of the weathering steel for a paint-free photovoltaic bracket is ≤6.0mm.

[0073] The hot metal is desulfurized by KR and then smelted in a 210-ton converter. It is then argon-blown in a ladle, refined in an LF furnace, vacuum-treated in RH, and continuously cast into 230 mm slabs. The slabs are stacked and cooled for 48 hours, reheated, and rough-rolled for 5 times. They are then thermomechanically controlled rolled and cooled in a 7-stand 2250 continuous rolling unit. The hot rolled coils are 2 mm and 4 mm thick.

[0074] The chemical composition of the steel for the unpainted photovoltaic bracket of Examples 1-3 is shown in Table 1, and the chemical composition of the steel of Comparative Examples 1-4 is shown in Table 1. The controlled rolling and controlled cooling process parameters are shown in Table 2, the mechanical properties are shown in Table 3, and the cycle infiltration test results are shown in Table 4.

[0075] Table 1 Chemical composition of the steel for the unpainted photovoltaic bracket of Examples 1-3 and the comparative steel. (The mass of each element is expressed in percentage, with the remainder being Fe and unavoidable impurity elements)

[0076]

[0077] Table 2

[0078]

[0079] Test Section

[0080] The coated weathering steel for photovoltaic brackets prepared in the examples and comparative examples were subjected to mechanical property tests according to GB / T 228.1, and the results in Table 3 were obtained.

[0081] The weathering steel for the coated photovoltaic bracket prepared in the embodiment and the comparative example was tested according to the GB / T19292.1 method to obtain the corrosion thickness loss data in Table 4.

[0082] Table 3 shows the weather-resistant mechanical properties test results of the coated photovoltaic brackets prepared in the embodiments and comparative examples.

[0083]

[0084] Table 4 Corrosion thickness loss data of weathering steel for coated photovoltaic brackets prepared in the embodiments and comparative examples.

[0085]

[0086] The above measured performance parameters are average values.

[0087] Figure 1 A micrograph of weathering steel for a paint-free photovoltaic support having a thickness of 2 mm according to an embodiment of the present application is shown. Figure 2 A micrograph of weathering steel for a paint-free photovoltaic support having a thickness of 4 mm according to an embodiment of the present application is shown. Figure 1 and Figure 2It shows that the grain size of weathering steel used in paint-free photovoltaic brackets is smaller, which is beneficial to improving corrosion resistance.

[0088] Figure 3 The corrosion morphology of the weathering steel for the paint-free photovoltaic bracket of the embodiment and the comparative example of the present application is shown. The hanging pieces of the weathering steel for the paint-free photovoltaic bracket of the embodiment and the comparative example were subjected to a wall hanging experiment at the Haibin Longyuan Power Plant in Zhanhua District, Binzhou. The morphology of the hanging pieces was 3m in the splash zone for 5 years. Among them, a is the weathering steel for the paint-free photovoltaic bracket of embodiment 1, b is the weathering steel for the paint-free photovoltaic bracket of embodiment 2, and c is the weathering steel for the paint-free photovoltaic bracket of comparative example 1. The experimental corrosion morphology can be seen from the morphology, which shows that the embodiments 1-2 are more corrosion-resistant than comparative example 1.

[0089] The above are only specific implementations of the present application, but the protection scope of the present application is not limited thereto, and any familiarity with the present technology or replacement should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A weathering steel for a non-painted photovoltaic support, characterized in that: The chemical composition of the weathering steel for the paint-free photovoltaic bracket includes, by mass percentage: carbon: 0.07%-0.09%, silicon: 0.20%-0.30%, manganese: 1.0-1.1%, sulfur ≤0.003%, phosphorus: 0.07%-0.09%, titanium: 0.040%-0.065%, chromium: 1.0%-1.1%, copper: 0.23%-0.28%, molybdenum: 0.12%-0.16%, aluminum: 0.55%-0.65%, antimony: 0.08%-0.12%, nitrogen ≤0.0045%, oxygen ≤0.0015%, hydrogen ≤0.00015%, and the rest are Fe and unavoidable impurity elements; the thickness of the weathering steel for the paint-free photovoltaic bracket is ≤6.0mm.

2. The weathering steel for a paint-free photovoltaic support according to claim 1 is characterized in that: The chemical composition of the weathering steel for the paint-free photovoltaic bracket includes, by mass percentage: carbon: 0.075%-0.085%, silicon: 0.20%-0.30%, manganese: 1.0-1.1%, sulfur ≤0.003%, phosphorus: 0.07%-0.09%, titanium: 0.040%-0.065%, chromium: 1.0%-1.1%, copper: 0.23%-0.28%, molybdenum: 0.13%-0.15%, aluminum: 0.58%-0.62%, antimony: 0.08%-0.12%, nitrogen ≤0.0045%, oxygen ≤0.0015%, hydrogen ≤0.00015%, and the rest are Fe and unavoidable impurity elements.

3. The weathering steel for a paint-free photovoltaic support according to claim 1 is characterized in that: The weathering index of the weathering steel for the coated photovoltaic support is greater than 8.

0.

4. The weathering steel for a paint-free photovoltaic support according to claim 1 is characterized in that: The metallographic structure of the weathering steel for coating photovoltaic brackets includes a two-phase composite structure of 5% to 15% ferrite and 85%-95% bainite by volume fraction; the grain size of the weathering steel for coating photovoltaic brackets is 8 to 10 levels.

5. The weathering steel for a paint-free photovoltaic support according to claim 1 is characterized in that: The yield strength of the weathering steel for the paint-free photovoltaic bracket is greater than or equal to 550 MPa, the tensile strength is greater than or equal to 600 MPa, the elongation is greater than or equal to 16%, and the -20°C KV2 impact energy is greater than or equal to 47J.

6. A method for preparing weathering steel for a coating-free photovoltaic support as claimed in any one of claims 1 to 5, characterized in that: The method comprises: The molten steel is subjected to converter smelting to obtain converter molten steel; The converter molten steel is subjected to LF refining and RH vacuum treatment to obtain tundish molten steel; Continuously casting the molten steel in the tundish to obtain a slab; The slab is heated, rolled, laminar-cooled and coiled to obtain the weathering steel for the coating-free photovoltaic support; The rolling includes rough rolling and finish rolling, the temperature of the rough rolling start is 1150-1180°C, the temperature of the rough rolling final rolling is 1050-1090°C, the temperature of the finish rolling start is 1030-1070°C, the finish rolling final rolling is 890-910°C, and laminar cooling is carried out after the final rolling, and the final cooling is carried out to 575-590°C for coiling.

7. The preparation method according to claim 6, characterized in that: After the converter smelting, the method further comprises: passing the converter molten iron through a ladle and blowing argon, and the temperature at the end point of the argon station is controlled to be greater than 1535°C.

8. The preparation method according to claim 6, characterized in that: RH vacuum treatment includes: vacuum degree requirement ≤133MPa, RH cycle time 20-30min, RH outgoing pouring furnace temperature 1570-1580℃, RH outgoing continuous pouring temperature 1558-1580℃.

9. The preparation method according to claim 6, characterized in that: The heating temperature of the slab is within the range of 1180-1230° C., and the slab is kept at this temperature for more than 20 minutes.

10. A paint-free photovoltaic bracket, characterized in that: The method is prepared by processing the weathering steel for paint-free photovoltaic support described in any one of claims 1 to 5 or the weathering steel for paint-free photovoltaic support prepared by the preparation method described in any one of claims 6 to 9.

Citation Information

Cited By

  • Coating-free low-cost high-strength weather-resistant steel plate for photovoltaic support and preparation method of high-strength weather-resistant steel plate

    CN121272298A

  • A coating-free, low-cost high-strength weather-resistant steel plate for photovoltaic brackets and its preparation method

    CN121272298B